Setting of import tolerances for deltamethrin in mangoes and papayas. (16th March 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer SAS submitted a request to the competent national authority in Austria to set import tolerances for the active substance deltamethrin in mangoes and papayas. The data submitted in support of the request were found to be sufficient to derive maximum residue level (MRL) proposals for mangoes and papayas. Adequate analytical methods for enforcement are available to control the residues of deltamethrin (c is ‐deltamethrin) in plant matrices under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of deltamethrin according to the reported agricultural practices is unlikely to present a risk to consumer health. The risk assessment shall be regarded as indicative and affected by non‐standard uncertainties.